Strategies for Utilizing TikTok in Small and Medium Enterprises' Digital Marketing - Muhamad Al Faruq Abdullah; Wenny Desty Febrian; Didin Hikmah Perkasa; Lutfi Alhazami (Dinasti International Journal of Education Management And Social Science, 2024)
This research aims to determine how relevant and engaging content, engagement and interaction, trust and reputation influence the intention to follow or someone's desire to follow a TikTok account as an effective marketing tool for Small and Medium Enterprises (SMEs) in the digital era. Primary data was collected using questionnaires distributed to 95 respondents in DKI Jakarta. The data was analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (SmartPLS 3.0) to test all relationships between content and reputation variables affecting interaction, and whether interaction also affects the intention to follow. The findings of this study provide insights into the strategic use of TikTok for enhancing SME marketing efforts, emphasizing the importance of creating engaging content and building a trustworthy reputation to drive user engagement and following intentions.